Toward the Professionalization of Catholic High School Religion Teachers: An Assessment of Religion Teaching as a Profession - Cook, Timothy J.; Hudson, William J. (Catholic Education: A Journal of Inquiry and Practice, 2006)
This article assesses religion teaching as a profession in terms of selected characteristics that scholars agree are common to all professions. The characteristics that are addressed include essential service, call to serve, special knowledge and skills, specialized and advanced university training, public trust and status, code of ethics and performance standards, and professional organization. The research suggests that religion teaching satisfies two of the seven selected characteristics, namely the essential service and call to serve, but does not fully satisfy the other five. The main conclusion drawn is that steps must be taken to professionalize religion teaching. To that end, recommendations include the further development of a professional association for religion teachers, credentialing standards, and a certification/licensing scheme.